2008
DOI: 10.1007/s10705-008-9210-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conservation tillage, crop residue and cropping systems on changes in soil organic matter and maize–legume production: a case study in Teso District

Abstract: The effects of conservation tillage, crop residue and cropping systems on the changes in soil organic matter (SOM) and overall maize-legume production were investigated in western Kenya. The experiment was a split-split plot design with three replicates with crop residue management as main plots, cropping systems as sub-plots and nutrient levels as sub-sub plots. Nitrogen was applied in each treatment at two rates (0 and 60 kg N ha -1 ). Phosphorus was applied at 60 kg P/ha in all plots except two intercropped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Similar results have been observed by Govaerts et al (2009) andAnyanzwa et al (2010). These authors report that, compared with other combinations of tillage with residue management, no-till practices with residue mulching promote the build-up of SOC in the surface soil and increase the distribution of soil aggregates, increase stability, and increase direct infiltration.…”
Section: Physical and Chemical Characteristics Of Soilsupporting
confidence: 85%
“…Similar results have been observed by Govaerts et al (2009) andAnyanzwa et al (2010). These authors report that, compared with other combinations of tillage with residue management, no-till practices with residue mulching promote the build-up of SOC in the surface soil and increase the distribution of soil aggregates, increase stability, and increase direct infiltration.…”
Section: Physical and Chemical Characteristics Of Soilsupporting
confidence: 85%
“…Conventional methods of crop establishment and residue harvested treatments add no more carbon which might be ascribed due to continuous nutrient removal from the plot. But, the level of soil organic carbon was not much decreased in conventional or residue harvested plots also as suggested by various literatures (Anyanzwa et al, 2010;Ghosh et al, 2010), it was found as similar to initial level and sometime slightly increased. This might be due to initial low carbon content in soil and maintaining by roots (Du et al, 2009).…”
Section: Discussionsupporting
confidence: 62%
“…The variation of soil organic carbon sequestration also depends on difference in microbial populace, moisture and temperature fluctuation (Govaerts et al, 2009). Residue retention and tillage has key role in soil carbon conservation (Duiker and Lal, 1999;Anyanzwa et al, 2010;Du et al, 2009;Corsi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The application of cattle manure on Chernozems increases the ratio of humic acids to fulvic acids, accelerates the formation of the labile humic substance and improves the formation of humus with a high degree of polymerized compounds (Nardia et al 2004). SOM is also positively affected by diverse cropping systems (Havlin et al 1990;Campbell et al 1998;Powell and Unger 1998;Anyanzwa and Okalebo 2010).…”
mentioning
confidence: 99%